2014
DOI: 10.1128/jvi.02576-13
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of NF-κB-Mediated Inflammation in Severe Acute Respiratory Syndrome Coronavirus-Infected Mice Increases Survival

Abstract: bSevere acute respiratory syndrome coronavirus (SARS-CoV) is the etiological agent of a respiratory disease that has a 10% mortality rate. We previously showed that SARS-CoV lacking the E gene (SARS-CoV-⌬E) is attenuated in several animal model systems. Here, we show that absence of the E protein resulted in reduced expression of proinflammatory cytokines, decreased numbers of neutrophils in lung infiltrates, diminished lung pathology, and increased mouse survival, suggesting that lung inflammation contributed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
400
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 388 publications
(426 citation statements)
references
References 75 publications
11
400
0
6
Order By: Relevance
“…In the present study, we found that the expression of phospho-JNK in the cecum of model rats was significantly upregulated, and this was attenuated by treatment with berberine. Another TAK1 cascade, NF-kB, a protein responsible for cellular responses to stimuli such as cytokines, UV irradiation, free radicals, and viral or bacterial antigens and that plays a crucial role in regulating the immune response to infection (Brasier, 2006;Perkins, 2007;Yadav et al, 2013;Dediego et al, 2014), was also implicated in the anti-inflammation effect of berberine. Our results showed that the activation of NF-kB induced by abrasive surgery was significantly inhibited by berberine, as indicated by a decreased phospho-NF-kB expression.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we found that the expression of phospho-JNK in the cecum of model rats was significantly upregulated, and this was attenuated by treatment with berberine. Another TAK1 cascade, NF-kB, a protein responsible for cellular responses to stimuli such as cytokines, UV irradiation, free radicals, and viral or bacterial antigens and that plays a crucial role in regulating the immune response to infection (Brasier, 2006;Perkins, 2007;Yadav et al, 2013;Dediego et al, 2014), was also implicated in the anti-inflammation effect of berberine. Our results showed that the activation of NF-kB induced by abrasive surgery was significantly inhibited by berberine, as indicated by a decreased phospho-NF-kB expression.…”
Section: Discussionmentioning
confidence: 99%
“…This strategy was directly applied in the case of SARS-CoV using conventional mouse strains without the need for Tg mice expressing the human ACE2 receptor (Day et al, 2009;Frieman et al, 2012;Roberts et al, 2007). Mouse-adapted SARS-CoV obtained by passing the virus 15 times in mice (SARS-CoV-MA15) has been an excellent model as it reproduces very well the pathology caused by SARS-CoV in humans, including mortality (DeDiego et al, 2011(DeDiego et al, , 2014b. In contrast, in the case of MERS-CoV, the virus was grown in Tg or knockin humanized mice susceptible to MERS-CoV (K. Li, P. McCray, and S. Perlman, 2016, personal communication).…”
Section: Animal Models For Cov Vaccine and Antivirals Studiesmentioning
confidence: 99%
“…Some CoV proteins act as IFN antagonists by inhibiting its production or signaling (Fig. 2) (DeDiego et al, 2014b;Totura and Baric, 2012;Zhong et al, 2012). Potent cytokines involved in controlling viral infections and priming adaptive immune responses are generated in response to CoV infection (Totura and Baric, 2012;Zhou et al, 2015).…”
Section: Coronavirus Virulencementioning
confidence: 99%
“…At the C-terminal end, the residue most affected was Ala39, and a group of nearby residues. Interestingly, most of these C-terminal juxtamembrane residues (residues 38-43) form a conserved motif in RSV SH protein "A 39 ILNKL 43 ," suggesting that binding of the drug may not only alter channel activity. This binding site is located at the luminal-facing narrowest region of the channel lumen ( Figure 3B).…”
Section: Channel Activity Inhibitors Of Sars-cov E and Rsv Sh Proteinsmentioning
confidence: 99%
“…41 Infected cells by SARS-CoV ∆E underwent apoptosis more rapidly and to greater extent, showed upregulation of stress response genes, downregulation of inflammation genes, 42 and decreased nuclear factor kappa-light-chainenhancer of activated B cells-mediated inflammation response in infected cells and mice. 43 …”
mentioning
confidence: 99%